The Livelihood Practices and sustenance among Dongria Kondhs of Odisha: Livelihood Practices - Bocha, Kedarnath; Bharikar Kotnak, Srinivas (IJRDO - Journal of Social Science and Humanities Research, 2021)
The livelihood practices of tribes in India are poor and much more dependent upon forest and agriculture based with no technical skills. All their livelihood related activities are only confined to agriculture based products along with natural forest products. Odisha is famous for its tribal concentration. It gives shelter to 62 varieties of tribal communities located in different parts of the State. Among all the tribes, Kondhs top the list regarding numerical preponderance and one of the main divisions of the Kondhs tribe is the Dongria Kondhs. Dongria Kondhs were recognized as Particularly Vulnerable Tribal Group by government of India and they inhabit exclusively in the Niyamgiri hill ranges of Eastern Ghats. The Dongria Kondh largely relies on shifting cultivation, horticulture, collection of Minor Forest Produce (MFP) along with hunting and gathering for survival. They perform agriculture by indigenous method. The current research paper is empirical in nature based on the field study among Dongria Kondh tribal group of Rayagada district of Odisha state. To collect the primary data from the field schedules were extensively used and the research methods followed for study are interview, surveys, focus group discussion and observation. The present study made an attempt to sketch an outline of the various issues related to livelihood practices among Dongria Kondhs and their perspective towards sustenance.